Novel RETREG1 (FAM134B) founder allele is linked to HSAN2B and renal disease in a Turkish family. Issue 7 (24th March 2022) - Taşdelen, Elifcan; Calame, Daniel G.; Akay, Gulsen; Mitani, Tadahiro; Fatih, Jawid M.; Herman, Isabella; Du, Haowei; Coban‐Akdemir, Zeynep; Marafi, Dana; Jhangiani, Shalini N.; Posey, Jennifer E.; Gibbs, Richard A.; et al.
Abstract: Hereditary sensory and autonomic neuropathy type 2B (HSAN2B) is a rare autosomal recessive peripheral neuropathy caused by biallelic variants in RETREG1 (formerly FAM134B) . HSAN2B is characterized by sensory impairment resulting in skin ulcerations, amputations, and osteomyelitis as well as variable weakness, spasticity, and autonomic dysfunction. Here, we report four affected individuals with recurrent osteomyelitis, ulceration, and amputation of hands and feet, sensory neuropathy, hyperhidrosis, urinary incontinence, and renal failure from a family without any known shared parental ancestry. Due to the history of chronic recurrent multifocal osteomyelitis and microcytic anemia, a diagnosis of Majeed syndrome was considered; however, sequencing of LPIN2 was negative. Family‐based exome sequencing (ES) revealed a novel homozygous ultrarare RETREG1 variant NM_001034850.2:c.321G>A;p.Trp107Ter. Electrophysiological studies of the proband demonstrated axonal sensorimotor neuropathy predominantly in the lower extremities. Consistent with the lack of shared ancestry, the coefficient of inbreeding calculated from ES data was low ( F = 0.002), but absence of heterozygosity (AOH) analysis demonstrated a 7.2 Mb AOH block surrounding the variant consistent with a founder allele. Two of the four affected individuals had unexplained renal failure which has not been reported in HSAN2B cases to date. Therefore, this report describes a novel RETREG1 founder allele and suggests renal failure may be an unrecognized feature of the RETREG1 ‐disease spectrum.